2014
DOI: 10.21014/acta_imeko.v3i3.59
|View full text |Cite
|
Sign up to set email alerts
|

An approach to determining the Brinell hardness indentation diameter based on contact position

Abstract: Significant differences in Brinell hardness results have been observed worldwide, largely due to the curved surface at the indentation edge making it difficult to measure its diameter. The indenter/material contact boundary under the test force should be the basis for the Brinell indentation diameter; however, the contact boundary cannot be observed using an optical microscope after the indenter is removed as is required by the test methods. Finite element analysis (FEA) models were used to develop a method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
15

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 10 publications
0
3
0
15
Order By: Relevance
“…Additional FEM work by Ma [11] demonstrated that the correlation between the minimum peak of the slope change and the indenter/material contact boundary is consistent and independent of material parameters including the type of material, hardness level, and indentation edge pile-up or sink-in conditions.…”
Section: Modelling Brinell Indentationmentioning
confidence: 82%
See 2 more Smart Citations
“…Additional FEM work by Ma [11] demonstrated that the correlation between the minimum peak of the slope change and the indenter/material contact boundary is consistent and independent of material parameters including the type of material, hardness level, and indentation edge pile-up or sink-in conditions.…”
Section: Modelling Brinell Indentationmentioning
confidence: 82%
“…Ma [10] used finite element modeling (FEM) to identify the node location of the indenter/material contact boundary while under load, and then tracked the movement of the FEM node during the unloading process. The magnitude of the movement of the contact boundary has been reported by Ma [11] to vary depending on a material's strain hardening, and ratio of modulus and yield stress.…”
Section: Modelling Brinell Indentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Existen numerosos estudios sobre el fenómeno de pile-up o sink-in y las causas que lo producen [54,55,56,3,57,9,2,58,59]. Como resumen podemos señalar que el desplazamiento de la superficie en el límite de contacto, bajo la aplicación de la carga y en el estado de descarga, está relacionado, fundamentalmente, con el coeficiente de endurecimiento por deformación n y con el cociente entre el módulo de Young y el límite elástico Como ya se ha indicado, la norma UNE [1] establece que la dureza Brinell se determina a partir del cociente entre la fuerza de ensayo y el área de la superficie curva de la huella (4.5).…”
unclassified
“…Para ello, la norma considera que la huella adopta la forma de la esfera de indentación y el área de su superficie se calcula como un casquete esférico a partir del diámetro de la huella. Diversos investigadores [56,44,60,4,58,5,61] extrapolan de esta definición que el diámetro medido para determinar la dureza Brinell debe ser el del límite de contacto entre el indentador y el material durante la aplicación de la fuerza de ensayo. Siguiendo esta idea, debería realizarse la medición del diámetro en el punto identificado como A en la figura 5.7, correspondiente al punto más alejado del eje central de la huella que está en contacto con el indentador cuando la carga es máxima.…”
unclassified